Commodity indexes and the stock markets of the GCC countries - Samih Antoine Azar; Nazo Assadour Chopurian (Arab Economic and Business Journal, 2018)
Much research is devoted to the study of the effect of oil on GCC markets. The link is evident, although waning. Little is known about the effect of other commodities, maybe because intuitively they are thought not to impact significantly these markets. However a finding of independence, or no-relation, has many implications for portfolio construction. Theoretically, if commodity markets respond to similar shocks as oil, which is a commodity itself, one would expect a positive relation. A negative relation is possible if commodities are diversifiers, or hedges, or even safe havens for GCC stock markets. The purpose of this study is to delineate empirically the nexus between GCC stock markets and commodity indexes. The results show that commodity indexes are in effect strong diversifiers and safe havens for GCC stock markets. One can improve the performance of a stock portfolio in GCC markets by including commodity indexes or, by extension, their derivatives. In other terms the risk/return trade-off is favourable to GCC investors. In fact the opportunity that is provided by the inclusion of commodities is puzzling: how come there is such an untapped opportunity, i.e. why didn't the GCC stock markets condense, absorb, and price this opportunity?
Keywords: 330; GCC stock markets; Commodity indexes; Hedge; Safe haven; Diversifier; Symmetry